Effect Of Giving Date Drinks On The Increase In Hemoglobin In Pregnant Women With Anemia At Grandmed Lubuk Pakam Hospital - Raini Panjaitan; Nadia Husna; Alberta Dameyanti Zega; Annisa Aulia (JURNAL KEBIDANAN KESTRA (JKK), 2021)
Anemia is a disease associated with pregnant women. The incidence of anemia due to iron mineral deficiency. This studi aims to determine the effect of giving dates drink to increasing haemoglobin levels in pregnant women with anemia in Rumah Sakit Grandmed Lubuk Pakam. This research method is quasi experiment with pre and posttest design. The population in this study is pregnant women with anemia in Rumah Sakit Grandmed Lubuk Pakam. The sample is 38 people consisting. In the treatment group was given intervention dates drink as much as 240 ml every day for 10 days. From the result of this research the majority of haemoglobin levels increased.The average haemoglobin levels after giving dates drink of 10 mg/dl. The result of the analysis with T-test was obtained p Value 0,000, it can concluded that there is the effect of determine the effect of giving dates drink to increasing haemoglobin levels in pregnant women with anemia.